Effects of defeat and entrapment on suicide risk in university population: the role of rumination and sex - Silvestre Vidal, Inmaculada Nayara; Nieto, Marta; Ricarte, Jorge; Vizcaíno Alcantud, María Dolores; Hallford, David; Ros, Laura (PeerJ, 2024)
Background Suicide is recognized as a significant public health issue, with adolescents/young people being a risk group of concern. Taking the integrated motivational-volitional model as a reference, this study focuses on analyzing the association between defeat and entrapment, on the one hand, and suicide risk, on the other, in a university population without depressive symptoms, while also considering the role of rumination and sex. Method The survey study involved a community sample of 650 Spanish university students. A total of 524 students (150 men (Mage = 20.6, SD = 3.7) and 374 women (Mage = 20.4, SD = 3.6)) completed self-report measures of suicide risk, defeat, entrapment, and rumination. Results Defeat and entrapment were significantly associated with suicide risk, and higher rumination was both directly and indirectly associated with higher levels of entrapment through the variable of defeat. However, the effect of rumination on entrapment varied by sex. Conclusion Despite being a cross-sectional preliminary study, this work identifies important variables in the trajectory of suicidal ideation. Adolescence and young adulthood are a critical stage for intervening to reduce the risk of death by suicide, and this study provides findings that may inform preventive approaches.
Keywords: Suicide risk; Defeat; Entrapment; Rumination; University students